HUBUNGAN KECUKUPAN VITAMIN A, VITAMIN C, ZINK DAN KADAR HEMOGLOBIN DENGAN KESEGARAN JASMANI SISWA SMA NEGERI 4 SEMARANG - Fitria Nur Rakhmawati; Setyo Prihatin; Dyah Nur Subandriani; Ria Ambarwati Ambarwati (Poltekkes Kemenkes Semarang, 2017)
Background : Physical fitness is the ability of a person's body to perform daily work tasks without causing significant fatigue. The importance of physical fitness for schoolchildren and adolescents, among others, can increase the ability of the body organs, social emotional, sportsmanship and spirit of composition. One of the factors that affect physical freshness is the hemoglobin level. Adequacy of vitamins and minerals is also a factor that indirectly affects physical fitness.Objectives : Describe the relationship of sufficiency of vitamin A, vitamin C, zinc and hemoglobin levels with physical fitness students in Senior High School 4 Semarang.Method : This research type is analytical descriptive with Cross Sectional design. The number of respondents is 104 students. Respondents were selected by proportional stratified sampling. Dependent variable of this research is physical fitness, independent variable that is vitamin A sufficiency, vitamin C sufficiency, zinc adequacy and hemoglobin level. Data analysis using Rank Spearman test and multiple linear regression test.Results : There is a relationship between hemoglobin (p-value = 0,000) with physical fitness. There was no correlation between vitamin A adequacy (p-value = 0,788), vitamin C adequacy (p-value = 0,203), adequacy of zinc (p-value = 0,257) with physical fitness.Conclusion : Hemoglobin level is the most influential factor on physical fitness of Senior High School 4 Semarang students.